The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1117/1.jbo.29.s1.s11506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of skin tone on photoacoustic imaging and oximetry

Thomas R. Else,
Lina Hacker,
Janek Gröhl
et al.

Abstract: . Significance Photoacoustic imaging (PAI) provides contrast based on the concentration of optical absorbers in tissue, enabling the assessment of functional physiological parameters such as blood oxygen saturation ( ). Recent evidence suggests that variation in melanin levels in the epidermis leads to measurement biases in optical technologies, which could potentially limit the application of these biomarkers in diverse populations. Aim To … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Additionally, extending applicability to a wider range of tissue types and chromophores, beyond those included in its initial training, would be important. All of the animal studies undertaken here were in nude mice, which lack skin pigmentation, however, skin tone is a consideration that is gaining greater attention in the PAI community 53 and data from a range of skin tones would be needed to maximise applicability of VAN-GAN in future.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, extending applicability to a wider range of tissue types and chromophores, beyond those included in its initial training, would be important. All of the animal studies undertaken here were in nude mice, which lack skin pigmentation, however, skin tone is a consideration that is gaining greater attention in the PAI community 53 and data from a range of skin tones would be needed to maximise applicability of VAN-GAN in future.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that also NIRS devices (due to the similarity with pulse oximeters 25 ) and -more generallyall light-based devices might be influenced by skin pigmentation. Recent studies on the photoacoustic technique demonstrated measurement bias, including an overestimation of StO2, in darker skin types 26,27 .…”
Section: Introductionmentioning
confidence: 99%